Metodologi Fiqh Al-Hadis: Metode, Teknik Interpretasi dan Pendekatan Dalam Memahami Hadis - Yasir, Muhammad; Ashshiddiq, Nasiruddin; Samsudin, La Ode; Maidinn, Muhammad Sabir (Madani: Jurnal Ilmiah Multidisiplin, 2025)
regions and when the Prophet Muhammad died. Therefore, scholars tried hard to bridge these problems so that the science of fiqh al-hadith emerged. In addition to the problems above, another problem is because today's society really needs an explanation of the science of how to understand hadith or fiqh al-hadith, so that they do not get lost in a deviant understanding. The results of this study indicate that the methodology of understanding hadith is the science of procedures or methods that are scientific in nature to explore and understand religious teachings in the form of the will or messages of the Prophet Muhammad. precisely, which are contained in the hadiths narrated by him. This methodology of understanding hadith contains many tools, such as methods, interpretation techniques, and various approaches. In addition, the method of understanding hadith can be classified into four models. First, is the Tahlili method (analysis), namely explaining the hadiths of the Prophet Muhammad. by explaining all aspects contained in the hadith and explaining the meanings contained therein. Second, is the ijmali method, which is explaining or explaining the hadiths according to the order of the hadith books in a concise manner, but can represent the literal meaning of the hadith in a language that is easy to understand. Third, is the maudu'i method, which is a method of understanding the hadith by collecting the hadith in a particular theme. And the fourth, is the muqa>ran method, which is a method of understanding the hadith by: comparing hadiths that have the same or similar wording in the same case or have different wording in the same case.